2016
DOI: 10.5606/archrheumatol.2016.5736
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip Strength in Fibromyalgia

Abstract: Objectives:This study aims to compare the handgrip strength values of fibromyalgia (FM) patients and healthy individuals and to demonstrate the relationship between clinical factors and FM disease severity. Patients and methods: Twenty-five female patients (mean age 34±9.2 years; range 20 to 50 years) with FM and 23 age-and body mass index-similar healthy females (mean age 35.3±9.2 years; range 26 to 46) were included. Demographic characteristics of the subjects were recorded. Tender point count was noted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…We hypothesize that FM patients had a lower speed of finger tapping task than controls due to the interaction of several factors linked to pain condition. Moreover, studies focused on motor ability suggest that FM patients had low manual dexterity [41] and minor handgrip strength [13] compared to healthy subjects. In a study on the evaluation of the kinematic parameters of gait and balance, patients with FM showed impaired motor performance [40].…”
Section: Reduced Motor Performance and Motor Cortical Areas Activatiomentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that FM patients had a lower speed of finger tapping task than controls due to the interaction of several factors linked to pain condition. Moreover, studies focused on motor ability suggest that FM patients had low manual dexterity [41] and minor handgrip strength [13] compared to healthy subjects. In a study on the evaluation of the kinematic parameters of gait and balance, patients with FM showed impaired motor performance [40].…”
Section: Reduced Motor Performance and Motor Cortical Areas Activatiomentioning
confidence: 99%
“…Researchers suggest that motor activity leads to an improvement in the quality of life of patients [11,12] so exercise is recommended for the treatment of FM symptoms. Moreover, FM patients have a peculiar limitation of movement that can manifest itself with dysfunctions in muscle coordination, difficulty in postural control and reduced speed of motor performance [13,14]. However, patients suffering from chronic pain are unlikely to exercise because they fear the worsening of their painful condition [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The association between FM and reduced HGs has been demonstrated in different contexts 38,41,42 . Discordant data also exist, in which no associations between FM severity and reduced muscle performance, expressed in terms of isokinetic flexion-extension of the knee, has been demonstrated 43 .…”
Section: Discussionmentioning
confidence: 98%
“…The patients had lower grip strength, performed lesser repetitions with maximal grip pressure (dynamic endurance work), and kept their upper extremity in a fixed position for a lesser duration (static endurance work) as compared to the healthy matched controls. Köklü et al 23 reported that FMS patients had decreased handgrip strength as compared to the controls. Contrary to these studies, Akyol et al 19 did not find any difference between the FMS patients and healthy controls regarding handgrip strength.…”
Section: Discussionmentioning
confidence: 99%